A emancipação insuficiente da pessoa com deficiência. Diagnóstico Jurídico. Paradigma de ancoragem e o desafio da geração de intérpretes. - Bernardes, Luana Ferreira (2017)
The present study aims at analyzing the niches of protective inadequacy that surround the emancipatory technique provided to people with psychic and intellectual deficiency by the advent of the Statute for Persons with Disabilities (EPD), as the result of the reformulation of the original legal incapacity regime of the Civil Code of 2002 (CC/02). In order to achieve the guidelines of independence and moral autonomy, as enshrined in the Convention on the Rights of Persons with Disabilities (CDPD), as well as to guarantee the equal exercise of the rights and of the fundamental freedoms of the disabled person, the statutory law excluded the original incapacity regime. This regime sent people with mental and intellectual deficiency to the glass dome of the partial guardianship and established the presumption of full civil capacity. Although the emancipation, by means of legal capacity, is commendable to the free development of the subjective existential situations of the human person, it was carried out in an inconsequential and insufficient way. Without fixing the related protective obligations to the concrete vulnerability of the person with mental and intellectual disability as a subject of rights capable in the patrimonial sphere. Therefore, by means of bibliographical and documentary research and of the adoption of a deductive methodological procedure, this paper will attempt to demonstrate the damages that the incidence in insufficient protection, caused by the emancipation without precautions and own safeguards, can cause to the dignity and to the rights of persons with disabilities. At the end of the discussion, the legislative omission will be resolved through hermeneutical criteria, especially the dialogue of sources as an instrument for the protection of the vulnerable.